Exceptional rate capability from carbon‐encapsulated polyaniline supercapacitor electrodes. Issue 3 (29th May 2020) - Stott, Ash; Tas, Mehmet O.; Matsubara, Elaine Y.; Masteghin, Mateus G.; Rosolen, Jose M.; Sporea, Radu A.; Silva, S. Ravi P.; Agnese, Yohan Dall'
Abstract : A high‐rate capability carbon‐encapsulated polyaniline (PANI) composite is fabricated by a novel electrodeposition method of polyaniline on a carbon nanotube (CNT) forest, grown on carbon paper. This is followed by coating of an amorphous carbon layer via hydrothermal carbonization (HTC) of glucose, forming a three‐layer structure. We demonstrate that a slow scan rate, voltage‐restricted electrodeposition process can be used to produce a uniform PANI coating on individual CNTs throughout the network. The CNT forest structure offers excellent electronic and structural connection for the PANI nanofiber network, while the coating of amorphous carbon reduces electrode resistance, promoting enhanced electrochemical performance and reinforced structural stability during charging and discharging. The as‐prepared CNT/PANI/HTC composite exhibited a high specific capacitance of 571 F g −1 at 1 A g −1, and 557 F g −1 at 100 A g −1, whilst demonstrating a record rate capability of 98% capacitance retention, when the current density is increased 100‐fold. This advanced rate performance indicates that a slow electrodeposition process produces an electrochemically stable three‐layer composite with enhanced diffusion kinetics. Hence, the method developed in this work establishes further control on the electrochemical deposition of energy storage materials, for high‐rate capability. Abstract : Carbon‐encapsulated PANI structures show an exceptional high‐rate capability of 98% for current density of 1 A g −1 to 100 A g −1 . Low scan rate electrodeposition of PANI is used to synthesize conformal coatings on CNT forests, followed by a coating of an amorphous carbon layer, to enhance energy storage performance.